INTEGRATED APPROACH: TRUCKERS’ PARKING BAY FACILITY, AS ENVIRONMENTAL HAZARD IN SALGAA “WILD WEST” NAKURU, KENYA. - Michura, Eliud Garry (Kabarak University, 2012)
Globally, poorly constructed truckers parking bays cause environmental hazards. Well documentations show that transport workers and truck drivers in East Africa face much higher risk of hazards specifically HIV /AIDS spread than the general population. (Transport and the National AIDS Control Council in, 2005)Studies done in Kenya in small towns offering truckers stop and rest bay such as Mariakani, Voi, Mlolongo, Naivasha, Malaba and Busia, indicate that they face environmental hazards such as HIV/ AIDS, drug/ alcohol abuse among others Mainja, 2006)HIV Spread is one major hazard that perplex every society. Countries such as India, Thailand, Cambodia, Dominican republic face serious problems related to HIV/AIDs as a result of csw. Strategies in managing the HIV spread is proving successful – Integrated approach
Keywords: Truckers Parking bay; Nakuru